2011
DOI: 10.1186/1754-9493-5-28
|View full text |Cite
|
Sign up to set email alerts
|

Anatomical relations of the superficial sensory branches of the radial nerve: a cadaveric study with clinical implications

Abstract: BackgroundAnatomically, it is difficult to give a systematic description of the superficial branch of the radial nerve (SBRN). Our aim was to describe the exact relationship of the SBRN to fixed bony points of radial styloid and Lister's tubercle, and to the cephalic vein. We also compared our data with other international studies.MethodsThe study was a descriptive anatomical study. Twenty-five forearms were dissected. Measurements were made from predefined fixed reference points.ResultsThe mean distance to th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
23
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(27 citation statements)
references
References 7 publications
3
23
0
1
Order By: Relevance
“…1b). The landmarks and reference lines were determined by reference to the method described by Abrams et al (1992) and Samarakoon et al (2011).…”
Section: Methodsmentioning
confidence: 99%
“…1b). The landmarks and reference lines were determined by reference to the method described by Abrams et al (1992) and Samarakoon et al (2011).…”
Section: Methodsmentioning
confidence: 99%
“…Las caracterís-ticas de la comunicación observadas en todas las muestras, coinciden con el tipo I descrito por Loukas et al Similar resultado fue lo que describió Zaki (2006), al encontrar comunicación entre el RSNR y el RDNU en el 65% de los casos, sin embargo, no entrega detalles de las características del ramo comunicante. Por lo demás ninguno de los otros autores comoTellioglu et al (2000); Bianchi (2002); Ikiz & Uçerler (2004); Huanmanop et al(2007); Klitscher et al (2007); Robson et al (2008); Tryfonidis et al (2010); Samarakoon et al (2011);Casoli et al;Goto et al y Cavusoglu et al hicieron referencia a la existencia de la comunicación entre estos ramos. Se desconoce la existencia de estas diferencias tan notables, ya sea por tamaño de la muestra, variación individual de los cadáveres o método de detección.…”
Section: Discusionunclassified
“…These branches originated always distally to the tendon of extensor pollicis brevis muscle. Samarakoon et al (2011) dissected 25 wrists and forearms, and observed that in most of the samples (68%), the CV and the SBRN crossed each other at least once, and even twice. In a study by Robson et al (2008), the cephalic vein was closely related (<2 mm) with the SBRN in 80% of cases (20 of 25 dissections).…”
Section: Anatomymentioning
confidence: 99%